Chronic neutrophilic leukemia. Issue 1 (2nd January 2018) - Bredeweg, Arthur; Burch, Micah; Krause, John R.
ABSTRACT: Chronic neutrophilic leukemia is a rare myeloproliferative disorder characterized by a sustained peripheral blood neutrophilia, absence of the BCR/ABL oncoprotein, bone marrow hypercellularity with less than 5% myeloblasts and normal neutrophil maturation, and no dysplasia. This leukemia has been associated with mutations in the colony-stimulating factor 3 receptor (CSF3R) that may activate this receptor, leading to the proliferation of neutrophils that are the hallmark of chronic neutrophilic leukemia. We present a case of chronic neutrophilic leukemia and discuss the criteria for diagnosis and the significance of mutations found in this leukemia.